Entertainment Computing <U+0013> ICEC 2013 12th International Conference, ICEC 2013, Sô Paulo, Brazil, October 16-18, 2013. Proceedings - Anacleto, Junia C.; Clua, Esteban W. G.; Silva, Flavio S. Correa.; Fels, Sidney.; Yang, Hyun S. (Lecture Notes in Computer Science, 2013)
This book constitutes the refereed proceedings of the 12th International Conference on Entertainment Computing, ICEC 2013, held in Sao Paulo, Brazil, in October 2013. The 13 full papers, 6 short papers, 11 posters presented were carefully reviewed and selected from 75 submissions. In addition to these papers, the program featured 2 demos, 3 workshops, 3 tutorials and 3 art installations, also summarized in this book. The papers cover various topics in the multi-disciplinary field of entertainment computing.